Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) pada Karyawan Tiara Supermarket - Chusnul Izha Rahmatus Sholikhah; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Organisational citizenship behaviour (OCB) is an essential thing that employees must own to improve the effectiveness and efficiency of company performance. Several factors that can influence OCB are job satisfaction and organisational commitment. This study aims to explain the effect of job satisfaction and organisational commitment on retail companies. This research is quantitative, and the analysis technique used is multiple regression analysis using SPSS 26. The sampling technique used is the saturation sample technique and used 58 employees as a sample. The result shows that job satisfaction has a positive and significant effect on OCB and organisational commitment has a positive and insignificant impact on OCB. Simultaneously, job satisfaction and organisational commitment positively and significantly affect OCB. These results indicate that the company should pay attention to the job satisfaction of employees to improve OCB, which has a significant influence on achieving company goals. However, organisational commitment also needs to be considered by the company because it will impact other variables such as company performance or employee turnover.